PENGARUH STRES KERJA, KOMITMEN ORGANISASIONAL, DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN DI PT. XYZ - ADITYA PRATAMA, MUHAMMAD; ALFIANDY, ARIEF (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
The purpose of this study was to determine the effect of work stres, commitment, and leadership style variables on employee satisfaction at PT. Bimatama Teknik Mandiri for both permanent and non-permanent employees are accessed. 100 employees. Samples were taken as many as 80 respondents where all employees were permanent, using a non-probabilty sampling technique, namely purposive sampling. Using data collection techniques in the form of a questionnaire. Data analysis was carried out using the SPSS version 25 application program. Based on the results of the research conducted, it can be said that variable stress, organizational commitment, and leadership style have a significant effect on PT. Bimatama Teknik Mandiri.